ASSESSMENT OF RETINAL MICROVASCULAR ALTERATIONS IN INDIVIDUALS WITH AMNESTIC AND NONAMNESTIC MILD COGNITIVE IMPAIRMENT USING OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 7 (July 2022) - Robbins, Cason B.; Akrobetu, Dennis; Ma, Justin P.; Stinnett, Sandra S.; Soundararajan, Srinath; Liu, Andy J.; Johnson, Kim G.; Grewal, Dilraj S.; Fekrat, Sharon
Abstract : In this study of 112 eyes of 59 individuals with amnestic mild cognitive impairment (MCI), 32 eyes of 17 individuals with nonamnestic MCI, and 111 eyes of 56 cognitively normal controls, we show that individuals with amnestic MCI have decreased retinal perfusion density as detected using optical coherence tomography angiography. Abstract : Purpose: To assess retinal microvascular alterations in individuals with amnestic mild cognitive impairment (MCI) and nonamnestic MCI. Methods: One hundred twelve eyes of 59 amnestic MCI participants, 32 eyes of 17 nonamnestic MCI participants, and 111 eyes of 56 controls with normal cognition were included. Optical coherence tomography angiography vessel density and perfusion density in the Early Treatment Diabetic Retinopathy Study 3-mm circle and ring were assessed. Retinal thickness parameters including retinal nerve fiber layer thickness, ganglion cell-inner plexiform layer thickness, central subfield thickness, and subfoveal choroidal thickness were also analyzed. Multivariable generalized estimating equations were used for statistical analysis. Results: Perfusion density in the 3-mm inner ring was significantly lower in amnestic MCI patients when compared with nonamnestic MCI participants (0.29 ± 0.03 vs. 0.34 ± 0.09, P = 0.025) and controls with normal cognition (0.29 ± 0.03 vs. 0.39 ± 0.02, P < 0.001), after adjustment for age and sex as covariates. Vessel density, retinal nerve fiber layer thickness, ganglion cell-inner plexiform layer thickness, central subfield thickness, and subfoveal choroidal thickness did not differ among or between diagnostic groups. Conclusion: Perfusion density was significantly reduced in individuals with amnestic MCI, compared with those with nonamnestic MCI and controls with normal cognition.